Impact assessment of aquaculture in small reservoirs pilots in northern Ghana: a baseline technical report - Zane, Giulia; Buisson, Marie-Charlotte; Appiah, Sarah; Asare, G. (International Water Management Institute (IWMI). CGIAR Initiative on Aquatic Foods, 2024)
The CGIAR Resilient Aquatic Foods Systems Initiative (RAqFS) aims to enhance the resilience of aquatic food systems by addressing systemic challenges. As part of this initiative, the International Water Management Institute (IWMI) partnered with the CSIR Water Research Institute and the Fisheries Commission of Ghana in 2023 to co-design and implement an aquaculture pilot in four small reservoirs across four communities in the North-East Region of Ghana. The pilot project engaged groups of 10-15 individuals in each community, ensuring the inclusion of youth and women, and provided them with technical training and essential inputs to undertake tilapia cage culture. The groups cultivated fish in August-September 2023 and completed the first cycle in September-October 2024.